Study of the Physiological Dynamics of Cadmium Accumulation in Two Varieties of Rice with Different Cadmium-Accumulating Properties - Shangdu Zhang; Xiang Wu; Ju Peng; Xiufei Meng; Bangzhi Shi; Leliang Zhou; Lianyang Bai (Journal of Chemistry)
This study focused on cadmium (Cd) uptake by two rice varieties, Yuzhenxiang (YZX) and Xiangwanxian 12 (XWX), which differ in their capacity to accumulate Cd, i.e., XWX > YZX. Treatments with three different gradients of soil Cd concentrations showed that with the increase in soil Cd concentration gradient, the Cd content in each rice plant organ also increased, i.e., Cd-3 > Cd-2 > Cd-1. The trend in the Cd content of each organ was such that the farther the organ from the root, the lower its Cd content, i.e., root > stem and sheath > leaf > grain. We observed that for all four growth stages, the booting stage is the key stage in terms of Cd absorption, where the highest levels of accumulation are observed, that is, booting stage > full heading stage > tillering stage > maturity stage. Of the two cultivars, XWX had higher SOD, POD, and CAT activities but lower MDA content. In contaminated soils, SOD, POD, and CAT activities increased gradually with the increase in Cd concentration, while MDA content decreased, which indicated that the low Cd variety XWX had an advantage over the high Cd variety YZX. Through the comparative analysis of photosynthetic physiology, it was found that the low-Cd-accumulating rice variety XWX appeared more tolerant to Cd, while the high-Cd-accumulating rice YZX was more sensitive. Therefore, the low Cd rice variety XWX was more suitable for planting safe rice in Cd-polluted paddy fields.